1998
DOI: 10.1093/emboj/17.16.4829
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding and hydrolysis are essential to the function of the Hsp90 molecular chaperone invivo

Abstract: B.Panaretou and C.Prodromou contributed equally to this workHsp90 is an abundant molecular chaperone essential to the establishment of many cellular regulation and signal transduction systems, but remains one of the least well described chaperones. The biochemical mechanism of protein folding by Hsp90 is poorly understood, and the direct involvement of ATP has been particularly contentious. Here we demonstrate in vitro an inherent ATPase activity in both yeast Hsp90 and the Escherichia coli homologue HtpG, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
658
3
13

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 682 publications
(703 citation statements)
references
References 68 publications
22
658
3
13
Order By: Relevance
“…The additional conformational change in the HSP90\CDDP complex by ATP may cause a slight recovery of the chaperone activity or dissociation of HSP90 from CDDP. (ii) It has been shown that complete HSP90 possesses a chaperone activity in i o dependent on ATP binding and ATP hydrolysis [21,22]. The CDDP binding site was located in the COOH-terminal domain of HSP90 (this study).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The additional conformational change in the HSP90\CDDP complex by ATP may cause a slight recovery of the chaperone activity or dissociation of HSP90 from CDDP. (ii) It has been shown that complete HSP90 possesses a chaperone activity in i o dependent on ATP binding and ATP hydrolysis [21,22]. The CDDP binding site was located in the COOH-terminal domain of HSP90 (this study).…”
Section: Discussionmentioning
confidence: 61%
“…The chaperone activity of HSP90 is inhibited by ansamycin antibiotics (GA) [18]. Recently, it has been published that the in i o function of HSP90 is dependent on ATP binding and ATP hydrolysis [21,22]. Furthermore, an important result has been reported that HSP90 acts as a capacitor for morphological evolution [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All strains are derived from strain pp30#10 [21] [22], we deleted the gene encoding the export pump Pdr5 by using homologous recombination to replace the coding region with the loxP-LEU2-loxP cassette from plasmid pUG73 [23]. This generated yeast strain DP533.…”
Section: Yeast Strainsmentioning
confidence: 99%
“…Additionally, biochemical studies suggest that transitory interactions between two N-terminal domains of the Hsp90 homodimer occur in an ATP-dependent manner, and this provides the mechanistic basis for an ATPase-driven molecular clamp [13]. Mutations in this region that impair the ability of Hsp90 to either bind or hydrolyze ATP eliminate its chaperone activity [14]. The discovery that the antibiotics, radicicol and geldanamycin, inhibit the Hsp90-dependent activation of numerous regulatory and signal transduction proteins by occupying their ATP-binding sites was a revelation in antitumor research [15].…”
mentioning
confidence: 99%